Assistance in Preparing Financial Reports According to ISAK 35 to Increase Accountability and Management Nurul Islam Orphanage Tlogosari Semarang - Setiyono, Taufiq Andre; Solovida, Grace Tianna; Attiq, Khoirul (LPPM STKIP Kusuma Negara, 2024)
This PKM activity aimed to assist the Nurul Islam Orphanage Semarang in implementing ISAK 35 to increase financial accountability and transparency. This program also develops an Orphanage Accounting Report System (SALPA) to disclose the financial reports so other parties can access for any requirement. Through this program, the orphanage managers have been able to prepare structured financial reports according to ISAK 35 standards. Transparency of financial report has also increased, proven by SALPA system that enable common people accessed the financial reports, so that donor confidence increases and makes it easier for the orphanage financial managers in submitting other donations. Challenges in the integration of Notes to Financial Reports (CALK) remain, but the SALPA system has helped improve the quality of financial management significantly.